Two-year recombinant human growth hormone (rhGH) treatment is more effective in pre-pubertal compared to pubertal short children with X-linked hypophosphatemic rickets (XLHR). (October 2017) - Rothenbuhler, Anya; Esterle, Laure; Gueorguieva, Iva; Salles, Jean-Pierre; Mignot, Brigitte; Colle, Michel; Linglart, Agnes
Abstract: Context: Twenty-five to 40% of patients with well-controlled X-linked hypophosphatemic rickets (XLHR) have a final height under − 2 SDS. Previous studies have shown that recombinant human growth hormone (rhGH) treatment improves linear growth in short children with XLHR. Objective: We studied the effectiveness of rhGH treatment in children with XLHR in a larger cohort. Design: Monocentric, prospective, non-randomized trial. Setting: University hospital in France. Patients: 19 patients with XLHR and a mutation in the PHEX gene. Six male and 6 female Tanner stage 1 patients (age 6.1 ± 2.4 years) and 4 male and 3 female Tanner stage 2 patients (age 13.1 ± 1 years). At inclusion, height SDS was − 2.35 ± 0.8 SDS and growth velocity was − 1.12 ± 1.2 SDS. Intervention: 2 years of treatment with 67 mcg/kg/day of rhGH at initiation. Every three months rhGH dosage was adjusted using an IGF-1 dosing protocol. Main outcome measures: Comparison in change from baseline to year 2 in height and growth velocity. Results: Height SDS improved from − 2.35 ± 0.8 SDS at baseline, to − 1.62 ± 0.8 SDS ( p  = 0.01) after one and to − 1.2 ± 1 SDS ( p  = 0.04) after two years of rhGH treatment. There was a strong correlation (r 2  = 0.6104, p  < 0.0001) between the age of onset of rhGH treatment and the number of cm gained over the study period. Pre-pubertal patients height SDS improved compared to baseline height SDS after one (− 1.5 ± 0.7, p  < 0.03) and two (− 0.96 ± 1, p  < 0.03) years of rhGH treatment. In pubertal patients there was no significant improvement in height SDS after one year (− 1.75 ± 1) and after two years (− 1.7 ± 0.8) of rhGH treatment. Conclusion: Two-year rhGH treatment is effective to treat short stature in XLHR children. Pre-pubertal children responded better to rhGH. Clinical trial registration number: NCT02720770 Highlights: rhGH increases growth velocity and stature in short XLHR patients rhGH-induced cumulative increase in stature was + 1.3 SDS in the pre-pubertal group and + 0.7 SDS in the pubertal children absolute height gain over the 2 year treatment period in pre-pubertal patients is 6.4 cm and 3 cm in the pubertal patients